Analysis of Flood Events in the Batang Kuranji Watershed Environmental Based on Weather Radar - Aulia Rinadi; Heldi Heldi (Science and Environmental Journal for Postgraduate, 2021)
Floods often occur in several parts of Indonesia, including the city of Padang. The potential for flooding is very high because of the Batang Kuranji watershed. The main trigger for flooding is high-intensity rain that occurs over a long period. To understand the occurrence of heavy rains, one of the efforts made is weather radar analysis so that it can support the creation of impact-based weather early warnings. This study aims to 1) analyze the ability of weather radar to support impact-based weather early warnings; 2) Knowing what factors cause flooding; and 3) Knowing whether the weather early warning information has been disseminated to the public. The method used is Mixed Method. Radar data is processed using Rainbow Dart to obtain several products. The data is analyzed both quantitatively and qualitatively. The results show that weather radar can be used to analyze local scale weather and short duration so that it can be used as a reference for making weather early warnings. physical rivers, erosion, and sedimentation. Weather early warning information has not yet reached all levels of society.